A Review of Monkeypox Infection in LGBT Community - Nurul Nisa Ulfa (Universitas Islam Negeri Sumatera Utara, Medan, 2023)
The reappearance of the monkeypox virus in 2022 in 58 countries and Indonesia is no exception, which confirmed 1 case in patients post travelling abroad. The current monkeypox infection is still present, with symptoms that vary from person to person and are typically characterized by reddish rashes. Still, it is primarily confined to the genital, perigenital, and perianal areas. It manifests at various stages of development, in addition to transmission from animals caused by hunting activities or in LGBT ( Lesbian, Gay, Bisexual, and Transgender) communities that have unprotected sex and can be infected through semen and saliva. This review aims to find a relationship between the increasing number of monkeypox cases, especially in LGBT community, based on the literature study approach and case reports. One of the non-medicamentous ways is to reduce travelling abroad, especially in countries with many monkeypox cases. Preventing direct contact, such as abstaining from sex and using condoms, is also a way to reduce the morbidity of monkeypox infection, especially in LGBT community. The treatment has not proven effective, and the available vaccines, especially in Indonesia, are still limited. Only a few cases in Indonesia have been reported.